Pembuatan Portabel Energi Berbasis Panel Surya Sebagai Sumber Energi Listrik Alternatif Saat Darurat Bencana untuk Bandan Penanggulangan Bencana Daerah Yogyakarta (BPBD DIY) - Elvira Sukma Wahyuni; Muhammad Wahyu Fauzi; Moch. Lukman Ariansyah; Husein Mubarok (Journal of Appropriate Technology for Community Services, 2024)
Natural disasters are quite common in Indonesia, such as volcanic eruptions, tsunamis, earthquakes, and floods, this is because Indonesia is located between the three tectonic plates of the world (Indo-Australia, Eurasia and the Pacific). Disasters that often occur cause material losses such as damage to buildings and hamper the supply of primary needs, for example the need for electrical energy. The delay in the need for electrical energy after a natural disaster has caused the mobility of the community to be disrupted, for example lighting.The portable energy system that has been designed has proven to be quite effective in supplying electrical energy for the evacuation of victims of natural disasters. The test results show that portable energy can produce energy of 720Wh with a load scheme of using five 10Watt LED lights that operate for 12 hours/day and three charger stations operating for 4 hours/day. In the charging test using a solar panel with 120 Wp the device can be fully charged for 9 hours, but if the weather is cloudy, the solar panel cannot produce maximum power and results in less than optimal battery charge.Portable energy can have positive social and environmental impacts. Positive impact on the social sector, because it can provide a temporary supply of electrical power so that the electricity supply to the affected areas can operate normally.